COMPARISON OF PROTEIN C LEVELS IN HIV PATIENTS WITH CD4 VALUES <200 CELLS/µL AND CD4 VALUES ≥200 CELLS/µL IN HAJI ADAM MALIK GENERAL HOSPITAL MEDAN - Indah Afriwanty Simatupang, Riecke Loesnihari & Tambar Kembaren (International Journal of Research Science and Management, 2021)
Introduction: Human Immunodeficiency Virus infection is a rapidly growing disease that attacked CD4 as its cell target. The reduction of CD4 value was generally accompanied by abnormality of the coagulation system which one of the components was protein C. Some studies proved that there was a correlation between CD4 cell count and decreased protein activity C, but the data regarding protein C levels with varying CD4 counts were still limited. This study aimed to determine the comparison of protein C levels in HIV patients with CD4 values <200 cells/µl and CD4 values ≥200 cells/µl in Haji Adam Malik General Hospital Medan. Methods: This study was an analytical study with a cross-sectional design which was conducted from December 2019 until February 2020. Eligible study subjects were at least 18 years old HIV patients who had been confirmed by the 3-methods strategy. Protein C levels were examined by the Coatron A4 machine. Data analysis used independent T-test and Pearson correlation test. Results: Thirty-eight study subjects were obtained consisting of 81.6% men with an average age of 33.16. ± 10.74 years. The median levels of protein C and CD4 were 79.2% and 192.5 cells µL, respectively. There was a significant difference in protein C levels between both groups (p <0.001). Conclusion: There was a significant difference in protein C level between HIV/AIDS patients with CD4 <200 sel/µL dan CD4 ≥200 sel/µL (p <0.001).